The role of skin care procedures in acne treatment - Czarnecka-Operacz, Magdalena; Jakubowicz, Oliwia (Dermatology Review/Przegląd Dermatologiczny, 2010)
Acne vulgaris (acne) remains one of the most common skin diseases. It is estimated that acne is diagnosed in 80% of the population between 11 and 30 years of age. Treatment of acne is difficult and demands complex systemic and topical therapy selected appropriately in relation to the clinical status of the patient. It seems that supplementary treatment with a properly composed line of skin care products for acne prone skin is of great importance. These preparations reduce the number of skin lesions and skin dryness which frequently results from the basic treatment and, what is of special importance, they improve the quality of life of acne patients.